Efficacy of non-invasive brain stimulation in decreasing depression symptoms during the peripartum period: A systematic review. (August 2021) - Pacheco, Francisca; Guiomar, Raquel; Brunoni, Andre R.; Buhagiar, Rachel; Evagorou, Olympia; Roca-Lecumberri, Alba; Poleszczyk, Anna; Lambregtse-van den Berg, Mijke; Caparros-Gonzalez, Rafael A.; Fonseca, Ana; Osório, Ana; Soliman, Mahmoud; et al.
Abstract: Background: Non-invasive brain stimulation (NIBS) techniques have been suggested as alternative treatments to decrease depression symptoms during the perinatal period. These include brain stimulation techniques that do not require surgery and that are nonpharmacological and non-psychotherapeutic. NIBS with evidence of antidepressant effects include repetitive transcranial magnetic stimulation (rTMS), transcranial electric stimulation (TES) and electroconvulsive therapy (ECT). Objectives: This systematic review aims to summarize evidence on NIBS eﬃcacy, safety and acceptability in treating peripartum depression (PPD). Methods: We included randomized, non-randomized and case reports, that used NIBS during pregnancy and the postpartum. The reduction of depressive symptoms and neonatal safety were the primary and co-primary outcomes, respectively. Results: rTMS shows promising results for the treatment of PPD, with clinically signiﬁcant decreases in depressive symptoms between baseline and end of treatment and overall good acceptability. Although the safety profile for rTMS is adequate in the postpartum, caution is warranted during pregnancy. In TES, evidence on efficacy derives mostly from single-arm studies, compromising the encouraging findings. Further investigation is necessary concerning ECT, as clinical practice relies on clinical experience and is only described in low-quality case-reports. Limitations: The reduced number of controlled studies, the lack of complete datasets and the serious/high risk of bias of the reports warrant cautious interpretations. Conclusions and implications: Existing evidence is limited across NIBS techniques; comparative studies are lacking, and standard stimulation parameters are yet to be established. Although rTMS benefits from the most robust research, future multicenter randomized clinical trials are needed to determine the position of each NIBS strategy within the pathways of care.